Study of mechanical character and corrosion properties of La2O3 nanoparticle reinforced Ni-W composite coatings - Cheng, Xinyu; He, Yi; Song, Ruxia; Li, Hongjie; Liu, Bo; Zhou, Huilian; Yan, Liping (Colloids and surfaces. A, Physicochemical and engineering aspects, 2022)
In this paper, Ni-W/La2O3 composite coatings were successfully prepared by pulse electrodeposition technology. The effect of the nano-La2O3 content in the plating solution on the structure and properties of the plated layers were evaluated. We find that nano-La2O3 can improve the situation of structural defects such as microcracks in the coating and serve to increase the thickness of the coating. Meanwhile, the Ni-W/La2O3 (4 g‧L−1) composite coating has the smallest crystallite size (6.52 nm). Compared with the Ni-W composite coating, the microhardness of Ni-W/La2O3 (4 g‧L−1) composite coating increased by 38.61 % (the microhardness value is 682.30 Hv), while the friction coefficient decreased by 46.57 % (the average coefficient of friction is 0.246) and the corrosion rate decreased by 81.54 % (the corrosion rate is 0.0498 mm‧a−1). [Display omitted] •The hardness value of Ni-W/La2O3 (4 g‧L−1) composite coating increased by 38.61 %.•The COF of Ni-W/La2O3 (4 g‧L−1) composite coating decreased by 46.57 %.•The corrosion rate of Ni-W/La2O3 (4 g‧L−1) composite coating decreased by 81.54 %.